(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
India’s farming industry accounts for 13.9 percent of the country’s GDP and hires just under 54.6 percent of the workforce. Cultivation and Cooperation ministry, which is part of Agriculture Ministry, is the nodal body in charge of developing India’s agriculture market. The aim of the research is to learn about the current state of the Indian agriculture market, the numerous challenges and obstacles that farmers, the agro-industry, and governments face in developing agriculture in sensitive uncontrollable environments, as well as various government interventions, investments, and policies for agricultural production and the importance of agriculture in the Indian economy.